Temelj slovenske ustave - Svete, Sebastjan (Pravnik, 2025)
The Constitution, as a form of social contract, has, or should have, its substantive foundation in the overall moral, ethical, philosophical, religious, and doctrinal common denominator of the community that concludes it. Since the preamble is understood as a solemn introduction and justification of the Constitution, the author asks himself two research questions: first, what is the preamble of the Slovenian Constitution, that is, what is its role in the Slovenian constitutional order; and second, how does the preamble bind the courts in the interpretation of the law. The author asks whether the preamble indeed expresses the foundation of the social contract and what the preamble should contain if it is to constitute that foundation of the social contract. The preamble, together with the Slovenian Constitution, was formed in a common process of independence and fundamental constitutional transformation, in which we as a nation searched for the origins of our own selfhood and identity and redefined our national narrative. In doing so, we formed the substantive starting point, the foundation from which the constitutional order draws. The important question is whether the non-legal foundation on which we have based our constitutional order is binding in the interpretation of our legal order.
Keywords: constitution; družbena pogodba; ethical orientation; etično orientacijski okvir; framework; nacionalni program; narodni narativ; national narrative; national programme; preamble; preambula; social contract; ustava